A Mathematical Model for Analyzing the Spread of Infectious Diseases Using Differential Equations - Olufemi Adeyemi; Adebayo Ayodele; Folake Olanrewaju (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
The spread of infectious diseases has become a critical issue in public health, requiring effective mathematical models to understand and control their dynamics. This study aims to develop a mathematical model based on differential equations to analyze the transmission patterns of infectious diseases. By dividing the population into distinct compartments—susceptible, infected, and recovered—this model provides a framework to study disease progression. The methodology involves formulating a system of ordinary differential equations to represent interactions among these compartments, followed by numerical simulations to explore key parameters influencing disease spread. The findings reveal significant insights into the role of infection rate, recovery rate, and basic reproduction number in determining the outbreak's intensity and duration. These results highlight potential strategies for intervention, including vaccination and quarantine measures, to mitigate the impact of infectious diseases. The proposed model serves as a valuable tool for researchers and policymakers to predict and manage disease outbreaks, offering practical implications for public health planning.